Understanding the Creeping Crisis - Boin, Arjen; Ekengren, Magnus; Rhinard, Mark (Springer Nature, 2021)
This open access book explores a special species of trouble afflicting modern societies: creeping crises. These crises evolve over time, reveal themselves in different ways, and resist comprehensive responses despite periodic public attention. As a result, these crises continue to creep in front of our eyes. This book begins by defining the concept of a creeping crisis, showing how existing literature fails to properly define and explore this phenomenon and outlining the challenges such crises pose to practitioners. Drawing on ongoing research, this book presents a diverse set of case studies on: antimicrobial resistance, climate change-induced migration, energy extraction, big data, Covid-19, migration, foreign fighters, and cyberattacks. Each chapter explores how creeping crises come into existence, why they can develop unimpeded, and the consequences they bring in terms of damage and legitimacy loss. The book provides a proof-of-concept to help launch the systematic study of creeping crises. Our analysis helps academics understand a new species of threat and practitioners recognize and prepare for creeping crises.